Teaching Training Method of a Lower Limb Rehabilitation Robot. (25th March 2016) - Feng, Yongfei; Wang, Hongbo; Lu, Tingting; Vladareanuv, Victor; Li, Qi; Zhao, Chaosheng
This paper presents a new lower limb rehabilitation robot (hereafter, referred to as LLR-Ro) to help patients with lower limb disorder recover their movement function. Based on the ergonomics and kinematics principle, the motion of a human lower limb is analysed, which provides a theoretical basis for the leg mechanism design of LLR-Ro. This paper also proposes a teaching training method for improving the training performance of LLR-Ro. When a physician trains the lower limb of a patient, the acceleration data of the patient's lower limb motion will be collected through a wireless data acquisition system. The data can reproduce the movement trajectory of the physician rehabilitation training and this can be used as the training trajectory of LLR-Ro. The experiment results of this study demonstrate that the teaching training method is feasible. The theory analysis and experimental research of LLR-Ro lay the foundations for the future clinical application of this method.